CLUSTER APPROACH AND STATE-PRIVATE PARTNERSHIP IN THE SYSTEM OF DEVELOPMENT CONTINGENCY RUNDOWN AT THE RUSSIAN ENTERPRISES - R. T. Safiullina (Russian Journal of Economics and Law)
The theme is of high topicality as the cluster approach implementation is one of the techniques of development contingency rundown at modern enterprises. The most important aspects of cluster approach are defined, in particular, the influence of industrial cluster and the possibility to implement the state-private partnership as the techniques of contingency rundown of firms. Basing on the carried out research the recommendations are made for the possibility to transform some elements of an industrial cluster in the system of the firms' functioning and interaction.